BS EN 3526. Aerospace series. Steel 15CrMoV6 (1.7334). Air melted. Hardened and tempered. Sheet and strip. 0, 5 mm ≤ a ≤ 6 mm. 980 MPa ≤ Rm ≤ 1 180 MPa. (1st April 2021) - British Standards Institution,
No abstract available